Salinity minimum in the subsurface layers of the Japan Sea - Valery A. Sosnin; Natalia I. Rudykh (Известия ТИНРО)
Seasonal variability of vertical salinity distribution in the Japan Sea is considered. On the base of high accuracy data from the databases WODC-2013 (USA), JODC (Japan), and the databases of Far-Eastern State Hydrometeorological Institute and Pacific Oceanological Institute (Russia), several cases of salinity minimums are analyzed and interpreted taking into account seasonal variability of salinity profiles. High vertical homogeneity by salinity is noted for the Japan Sea waters, and the subsurface salinity minimum can be considered as a result of continuous changes of freshwater balance. It could be formed in the layers from the sea surface to 150-250 m as a temporary local extreme caused by prevalence of evaporation over precipitation on the sea surface in some seasons - that’s why it is observed seasonally. There is concluded that such conservative patterns as water masses are absent in the sea, at least in its active upper layers, but vertical salinity profiles are changing permanently under influence of changing freshwater fluxes, and their extremes appear or disappear in compliance with the dialectic laws.